VD_FINDINFO Réc-civile / 2017 / 5 vom 31. Januar 2017 - VD Tribunal cantonal (2017)
RÉCUSATION, AUTORITÉ DE RECOURS, AVOCAT, PROCÈS-VERBAL, COMPORTEMENT | 322 al. 1 CPC (CH), 47 al. 1 let. f CPC (CH), 50 al. 2 CPC (CH), 51 al. 1 CPC (CH), 8a al. 7 CDPJ